Formulasi Sediaan Krim Ekstrak Etanol Daun Cocor Bebek (Kalanchoe pinnata L.) Sebagai Penyembuh Luka Bakar Pada Kelinci - Waehama, Asma, Tanti Azizah S, M.Sc.,Apt, Suprapto, M.Sc.,Apt (2016)
Plants kalanchoe pinnata consist flvonoid advantage to healing burns. This study aims to determine the activity of the cream ethanolic extract of Kalanchoe pinnata leaf and determine the effect of the concentration of ethanolic extract of Kalanchoe pinnata leaf on the level effectiveness of the healing burns in rabbits. Extract of Kalanchoe pinnata leaf formulated into cream preparation type of O/W with various concentrations of 2.5% (F2), 5% (F3), 10% (F4). Cream preparations tested physical properties (organoleptic test, adhesion test, disperses power test, viscosity test, and pH test.) And the preparation of creams used in burns rabbit as many as five rabbit. Each backs of rabbits were divided into 6 burns, first is no treatment, second is the control cream base, third is a positive control, fourth till sixth are preparation with a concentration of F2, F3, and F4. The long data has the healing burns were statistically analyzed by Kruskal-Wallis test. The result of Kruskal- Wallis test that found 0,745 (p> 0,05) to tell the values no significant compared with the negative control, statistically meant that does not have significant activity and there is no difference effect between all treatment of healing burns, while descriptive results show preparations cream activity and cream with a concentration of 5 % faster in healing burns with a time of 22.0 ± 6.7 days , while cream kalanchoe pinnata leaf extract at a concentration of 2.5% and 10 % respectively is 23.8 ± 6.7 days and 25.6 ± 6.5 days.